THE ROLE OF DEBT COLLECTOR SERVICES IN WITHDRAWAL OF FIDUCIARY COLLATERAL IN FINANCING COMPANIES (Case Study on Finance in the City of Kediri) - Sunardi, Sunardi; Parmono, Budi; Afifuddin, Moh (Universitas Islam Malang, 2022)
, This finance company faces a dilemma when the consumer/customer defaults or is late or fails to pay. The leasing company will try to return its rights, namely goods that have become fiduciary guarantees. At first glance, it seems that there is a civil relationship, but we all know that efforts to restore the rights of these leasing companies are often difficult, in the end some of these companies use the services of debt collectors.Formulation of the problem how the role of debt collector services in withdrawing fiduciary guarantees at financing companies in Kediri City, the factors that cause finance companies to use debt collector services in withdrawing fiduciary guarantees in Kediri City, and the legal consequences of withdrawing fiduciary guarantees carried out by Debt Collectors. The method in this research is empirical juridical. The results of the research on the Role of Debt collector Services in Withdrawing Fiduciary Guarantees at Financing Companies in the City of Kediri. need each other to deal with bad credit problems between debtors who are in default and creditors of Financing Companies, but debt collectors solve bad credit problems for vehicles and to save company assets from being lost for practical reasons without having to go through legal channels and have to use a professional method and in accordance with regulations applicable.Factors That Cause Finance Companies to Use Debt collector Services in Withdrawing Fiduciary Guarantees in the City of Kediri. a) Because legal and legal means are not working, they are considered inefficient and ineffective. b) The lengthy process of law enforcement creates public disappointment. c) Courts cannot guarantee legal certainty and run short. d) Debt collectors are considered more able to work in a relatively short time and the success rate reaches 90%. Legal Consequences of Withdrawal of Fiduciary Guarantees Made by Debt Collectors. who take the object of fiduciary collateral by seizing and threatening the debtor, including committing a criminal act. This action is as regulated in Article 368 of the Criminal Code (Criminal law book). cause legal consequences which are punishable by imprisonment for a maximum of 9 (nine) months.Keywords. Financing institutions, bad loans, debt collectors